2013
DOI: 10.1590/s0004-27492013000600016
|View full text |Cite
|
Sign up to set email alerts
|

Quality of vision in refractive and cataract surgery, indirect measurers: review article

Abstract: Visual acuity is the measurement of an individual's ability to recognize details of an object in a space. Visual function measurements in clinical ophthalmology are limited by factors such as maximum contrast and so it might not adequately reflect the real vision conditions at that moment as well as the subjective aspects of the world perception by the patient. The objective of a successful vision-restoring surgery lies not only in gaining visual acuity lines, but also in vision quality. Therefore, refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…T he contrast sensitivity function is considered an im portant aspect of the visual perform ance and the ability to perform daily tasks 3,4 , and seem ed to decrease w ith aging, w hen patients w ere divided into different age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T he contrast sensitivity function is considered an im portant aspect of the visual perform ance and the ability to perform daily tasks 3,4 , and seem ed to decrease w ith aging, w hen patients w ere divided into different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This equipment employs the Functional Acuity Contrast Test -FACT protocol, considered one of the most suitable for clinical studies 4,6 . Its measurements are made by reading sine bars of high quality in the spatial frequencies of 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wavefront aberrations in human eyes are one of the most important factors that degrade retinal image quality so that the various components of the wavefront aberrations, and their interactions, should be carefully analysed. Previous studies have found partial compensation between the cornea and the internal optics .…”
Section: Introductionmentioning
confidence: 99%
“…The requirement for precise measurements and assessments of corneal topography is increasing. Most patients undergoing cataract or refractive surgery expect to experience excellent postoperative uncorrected visual acuity, [1] and for this purpose an accurate and precise examination of such patients’ ocular parameters is mandatory. [2] [6] In addition, corneal power is indispensable to analyzing the shape of the cornea and for fitting contact lenses.…”
Section: Introductionmentioning
confidence: 99%